Analysis of Maximum Capacity Calculation of Kota Station Traction Substations to Maximize MRT Jakarta Phase 2 Train Operations - Dian Samodrawati; Saddam Abdur Rahman (Fakultas Teknik Universitas Bhayangkara, 2021)
MRT Jakarta is one of the providers of rail transportation services in Jakarta, which is an absolute solution to the problem of congestion in Jakarta because mass transportation can transport people in large quantities in one trip so that by calculating the electrical power capacity to supply electricity to the MRT Jakarta train it is very important with the aim of predicting the pattern of train operation. This test includes calculating the use of traction substations with headway, namely 10, 7, 5, 3, and 1 minute, then the power usage of the train according to data from technical specifications and also required data on filling distances for Kota Station Traction Substations in Phase 2 construction documents, then an analysis is carried out for the ability of the traction substation that supplies train operators in Phase 2. After calculating and analyzing, concluded that under normal conditions the Kota Traction Substation can operate continuously with a headway operating pattern of 10, 7, 5, and 3 minutes, then in disturbance conditions, 1 TSS Off the Kota Traction Substation can operate continuously with an operating pattern. headway 10, 7, and 5 minutes, then in disturbance condition 2 TSS Off.